2017
DOI: 10.1111/cogs.12517
|View full text |Cite
|
Sign up to set email alerts
|

Two Models of Moral Judgment

Abstract: This paper compares two theories and their two corresponding computational models of human moral judgment. In order to better address psychological realism and generality of theories of moral judgment, more detailed and more psychologically nuanced models are needed. In particular, a motivationally based theory of moral judgment (and its corresponding computational model) is developed in this paper that provides a more accurate account of human moral judgment than an existing emotion-reason conflict theory. Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 91 publications
(213 reference statements)
0
5
0
Order By: Relevance
“…Our regression analyses showed that, consistent with previous studies ( Voiklis and Malle, 2017 ), YA’s moral/conventional judgments seem to rely on the agent’s intentions and on an analysis of mental states (especially in terms of their assessment of the intensity of others’ emotions), but also on the analysis of their own mental state (in terms of emotions they feel). This result suggests a double influence of the “social brain” and the “emotional brain” ( Young and Dungan, 2012 ) in moral/conventional judgments ( Greene et al, 2001 ; Nichols, 2002 ; Moll et al, 2008 ; Tasso et al, 2017 ; Bretz and Sun, 2018 ). In contrast, OA’s moral/conventional judgments did not rely on their own emotions but only on the analysis of others’ mental states (in terms of the others’ intentionality and the intensity of others’ emotions).…”
Section: Discussionmentioning
confidence: 97%
“…Our regression analyses showed that, consistent with previous studies ( Voiklis and Malle, 2017 ), YA’s moral/conventional judgments seem to rely on the agent’s intentions and on an analysis of mental states (especially in terms of their assessment of the intensity of others’ emotions), but also on the analysis of their own mental state (in terms of emotions they feel). This result suggests a double influence of the “social brain” and the “emotional brain” ( Young and Dungan, 2012 ) in moral/conventional judgments ( Greene et al, 2001 ; Nichols, 2002 ; Moll et al, 2008 ; Tasso et al, 2017 ; Bretz and Sun, 2018 ). In contrast, OA’s moral/conventional judgments did not rely on their own emotions but only on the analysis of others’ mental states (in terms of the others’ intentionality and the intensity of others’ emotions).…”
Section: Discussionmentioning
confidence: 97%
“…Indeed, patients showed less utilitarian behaviors and more emotion-based evaluations compared to healthy subjects. Although moral judgment is considered to occur quickly as an intuitive automatic response, based on deontological principles rather than being a conscious and rational reasoning process that follows a careful evaluation of the moral situation (Haidt, 2001), the definition of the acceptability of moral actions entails the engagement of specific decision-making competences to calculate the preferable solution (Bretz and Sun, 2018). Rational calculation of moral actions usually results in utilitarian solutions (the greatest good for the greatest number), while emotion-based evaluations imply taking non-utilitarian behaviors, as seen in our patient sample.…”
Section: Discussionmentioning
confidence: 99%
“…Also, in personal life, the story's hero and the one who is reasoning are the same individuals. Furthermore, the PSYCHIATRY AND CLINICAL PSYCHOLOGY emotions [33,44,45], sense of duty [46], thought of the outcome, and the fate of the closest people [32] affects the individual's decision and maybe a moral act independent of moral judgment in reality [49].…”
Section: Discussionmentioning
confidence: 99%